The Effectiveness of Emotional Intelligence Program on Psychological Manifestations in Patients with Oppositional Defiant Disorder - Golestanpour, Mahdieh; Salahian , Afshin (International Journal of Applied Behavioral Sciences, 2024)
Background and Aim:Oppositional defiant disorder (ODD) is associated with violence, disobedience, stubbornness, anger, and aggression. The role of promoting emotional intelligence on psychological manifestations such as aggression and social anxiety has not been studied. Materials and Methods:In a pilot randomized clinical trial, during October 2017 to March 2018, 30 adolescents with a diagnosis of ODD were purposefully selected. Subjects were divided into two groups through block randomization (BR). Emotional intelligence education was provided to the experimental group in the form of eight one-hour weekly sessions and the control group was placed on a waiting list. Participants answered the questionnaires of emotional intelligence, social anxiety, and aggression in two time periods before and after treatment. Data were analyzed using multivariate analysis of covariance in SPSS software version 21. Results:Preliminary results showed that the intervention of emotional intelligence education had a significant effect on the indicators of aggression, emotional intelligence, and social anxiety (all p’s <0.05). Secondary outcomes showed that this intervention was effective on the indicators of physical discomfort and social anxiety (p >0.05). Conclusion:The findings of the present study indicate the effective role of emotional intelligence education on psychological indices such as aggression, emotional intelligence and social anxiety. These findings could be associated with clinical applications in the prevention and treatment of oppositional defiant disorder in adolescents.